Performance evaluation and life cycle analysis of new solar thermal absorption air conditioning system. (February 2020) - Rahman, Shek; Said, Zafar; Issa, Salah
Abstract: The aim of this project is to design a solar thermal absorption air conditioning system that operates under UAE climate conditions. In absorption system, compressor which is normally used in conventional AC system, replaced by a chemical cycle that consists of a generator, absorber, pump, and expansion valve, while the rest of the components such as the evaporator, condenser, and expansion valve remain the same as conventional AC system. In this design, the water and lithium bromide pair is used as a refrigerant and absorbent, respectively. The generator is driven by an evacuated solar collector to heat the lithium bromide in the chemical cycle, while a solar PV panel, which ensures that the system works 100% by solar energy, drives the pumps and fans. An energy storage device also incorporated in the system to run it round the clock. An experimental investigation of the proposed design is presented in the paper. Results suggest that the proposed design match well to meet the cooling load demand which was about 300 watts. Furthermore, the system able to provide a desired as well as uniform comforts temperature at about 23 °C inside the room. The system COP was calculated to be 0.51. Life cycle analyses were also carried out using Eco Audit CES Edu pack software to study the viability of the new design. The results showed that the proposed new system is economically viable and environmentally friendly.